THE ROLE OF AUDIOBOOKS AS A MEDIA IN ENGLISH FOREIGN LANGUAGE TEACHING - Tania Todorova (Издател)
The monograph “The role of audiobooks as a medium in the teaching of English as a foreign language” by Dr. Teodora Genova from the University of Library Science and Information Technology examines audiobooks as a medium in correlation with the other two book formats – printed and electronic books – and offers a clear view of the place of audiobooks as part of mobile assisted foreign language learning. Here the media is considered multi-dimensionally with its myriad benefits and functions in various aspects of its application. The book represents the first experience in which this pedagogical tool can be successfully used for the purposes of learning a foreign language in harmony with the constantly changing modern information and communication technologies. In addition, the author of the monograph dwells on recent trends in the dynamically developing status of audiobooks in recent years, influenced by the COVID-19 pandemic. The theoretical part of the monographic work is supplemented with an exposition and analysis of the results of five large-scale surveys conducted in Bulgaria on the attitudes towards the use of audiobooks in English foreign language teaching.